Diet and Pre-eclampsia: A Prospective Multicentre Case–Control Study in Ethiopia. Issue 6 (June 2015) - Endeshaw, Mulualem; Abebe, Fantu; Bedimo, Melkamu; Asart, Anemaw
Abstract Introduction Pre-eclampsia is one of the most commonly encountered hypertensive disorders of pregnancy that accounts for 20–80% of maternal mortality in developing countries, including Ethiopia. For many years, diet has been suggested to play a role in pre-eclampsia. However, the hypotheses have been diverse with inconsistent results across studies, and this has not been studied in Ethiopia. Objectives The objective of this study was to determine the effect of dietary habits on the incidence of pre-eclampsia in Bahir Dar, Ethiopia Methods A prospective multicentre unmatched case–control study was conducted among 453 (151 cases and 302 controls) pregnant women attending antepartum or intrapartum care in public health facilities of Bahir Dar City from June to September 2014. The interviewer conducted a face-to-face interview, measured the mid-upper arm circumference (MUAC) and collected the mid-pregnancy haemoglobin level from clinical notes using a standardized and pretested questionnaire. Epi Info 3.5.3 was used for data entry and cleaning, while IBM SPSS Statistics 20 was used for data analysis. Backward stepwise unconditional logistic regression analysis was employed to determine the strength of association of predictive variables with the outcome variable and to control for the effect of confounding variables. A P-value ≤0.05 was considered statistically significant. Result For every 1-cm increase of MUAC, there was an increase in the incidence rate of pre-eclampsia by a factor of 1.35 (adjusted odds ratio (AOR)=1.35, 95% confidence interval (CI): 1.21, 1.51). A higher incidence of pre-eclampsia was found in women who reported to have consumed coffee daily during pregnancy (AOR=1.78, 95% CI: 1.20, 3.05). Similarly, for women who had anaemia during the first trimester, the incidence of pre-eclampsia was 2.5 times higher than their counterparts (AOR=2.47, 95% CI: 1.12, 7.61). This study also revealed consumption of fruit or vegetables at least three times a week during pregnancy to be protective against pre-eclampsia (AOR=0.51, 95% CI: 0.29, 0.91; AOR=0.46, 95% CI: 0.24, 0.90, respectively). In addition, compliance with folate intake during pregnancy has shown a significant independent effect on the prevention of pre-eclampsia in this study (AOR=0.16, 95% CI: 0.08, 0.29). Conclusion and recommendation Adequate vegetable and fruit consumption and compliance with folate intake during pregnancy are independent protective factors against pre-eclampsia. On the other hand, higher MUAC, anaemia and daily coffee intake during pregnancy are risk factors for the development of pre-eclampsia. Audience-specific education and promotion of the use of the protective factors identified in this study should be prioritized. The risk factors identified can be used for prediction and early diagnoses of pre-eclampsia allowing timely interventions to be performed to minimize deaths associated with severe pre-eclampsia/eclampsia.